2023
DOI: 10.1021/acsami.3c04339
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-Driven Self-Propelled Devices Fabricated by a Femtosecond Laser

Abstract: Self-propelled autonomous devices have broad application prospects in energy conservation, environmental protection, and biomedical engineering. Nevertheless, the driving force always consumes external energy or special chemicals. Here, a novel and green droplet-driven device (DDD) consisting of superhydrophilic triangles on a superhydrophobic plate is processed only by a femtosecond laser. The water droplet flows into water along the superhydrophilic channel and forms a jet to provide driving force for the DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…In recent years, fluid transportation has gradually gained attention because of the development of precision medicine, micro-devices, and green energy collection. Researchers found that surfaces for water and gas transportation had numerous applications such as fog collection, heat transfer, drug transportation, and so on [1][2][3][4][5][6][7]. However, when a water droplet touches a solid surface, it will perform some indeterminate behaviors, such as impacting, jumping, trapping, and spreading.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fluid transportation has gradually gained attention because of the development of precision medicine, micro-devices, and green energy collection. Researchers found that surfaces for water and gas transportation had numerous applications such as fog collection, heat transfer, drug transportation, and so on [1][2][3][4][5][6][7]. However, when a water droplet touches a solid surface, it will perform some indeterminate behaviors, such as impacting, jumping, trapping, and spreading.…”
Section: Introductionmentioning
confidence: 99%